Evidenzbasierte Politikberatung - Klaus F. Zimmermann (Vierteljahrshefte zur Wirtschaftsforschung, 2011)
The essay reports the personal experience of providing policy advice in the early years of the labor market reforms at the beginning of the last decade after the scientific reorientation carried out by the German research institutes on the request of the German Research Council. The Council was insisting on a close connection between research and policy advice, which was implemented subsequently by the institutes. This has lead to a new understanding of policy advice, which is based on academic research and empirical evidence. The willingness of policymakers to accept this new paradigm has contributed significantly to the success of the labor market reform policy. – – Der Beitrag berichtet über persönliche Erfahrungen aus der Politikberatung in der Frühphase der Arbeitsmarktreformen zu Beginn der letzten Dekade vor dem Hintergrund der wissenschaftlichen Neuorientierung der Wirtschaftsforschungsinstitute aufgrund von Auflagen des Wissenschaftsrates. Der Rat hatte zuvor eine enge Verknüpfung zwischen Forschung und Beratung gefordert, die von den Instituten zügig umgesetzt wurde. Dies führte zu einem neuen Politikberatungsverständnis, dessen Fokus auf wissenschaftlicher Basis und empirischer Evidenz liegt. Die Bereitschaft der Politik, dieses neue Beratungsverständnis anzunehmen, hat zum Erfolg der Reformpolitik am Arbeitsmarkt wesentlich beigetragen.
Keywords: A11; B4; J48; 330; Role of economists; methodology of policy advice; labor reform policies; Wirtschaftspolitische Beratung; Wirtschaftsforschung; Empirische Methode; Arbeitsmarktpolitik; Reform; Deutschland